Ekstrak Labu Siam (Sechium edule) Dapat Menurunkan Kadar Serum Malondialdehid pada Tikus Putih (Rattus norvegicus) yang Diberikan Pakan Kolesterol (Journal of Telenursing (JOTING), 2022)
This study aimed to analyze the effect of chayote extract (Sechium edule) on malondialdehyde serum levels in white rats (Rattus norvegicus) fed a high-cholesterol diet and to prove the antioxidant content of chayote. The method used is experimental with a post-test-only control group design. This study used white rats, which were divided into five groups. The results of this study indicate that the administration of chayote extract at a dose of 0.25 g/kg BW and 0.5 g/kg BW can reduce the serum MDA concentration, although it is not statistically significant, while the administration of a chayote extract at a dose of 0.75 g/Kg BW can significantly reduce serum MDA levels in white rats induced by hypercholesterolemia. In conclusion, chayote extract at a dose of 0.75 g/kg BW can reduce blood MDA serum levels in white rats induced by hypercholesterolemia.Keywords: Chayote Extract, Hypercholesterolemia, Malondialdehyde